Hormonal Replacement Therapy and the Risk of Lung Cancer in Women: An Adaptive Meta-analysis of Cohort Studies - Jong-Myon Bae; Eun Hee Kim (Korean Society for Preventive Medicine, 2015)
Objectives: Approximately 10% to 15% of lung cancer cases occur in never-smokers. Hormonal factors have been suggested to lead to an elevated risk of lung cancer in women. This systematic review (SR) aimed to investigate the association between hormonal replacement therapy (HRT) and the risk of lung cancer in women using cohort studies. Methods: We first obtained previous SR articles on this topic. Based on these studies we made a list of refereed, cited, and related articles using the PubMed and Scopus databases. All cohort studies that evaluated the relative risk of HRT exposure on lung cancer occurrence in women were selected. Estimate of summary effect size (sES) with 95% confidence intervals (CIs) were calculated. Results: A total of 14 cohort studies were finally selected. A random effect model was applied due to heterogeneity (I-squared, 64.3%). The sES of the 14 articles evaluating the impact of HRT exposure on lung cancer occurrence in women indicated no statistically significant increase in lung cancer risk (sES, 0.99; 95% CI, 0.90 to 1.09). Conclusions: These results showed that HRT history had no effect on the risk of lung cancer in women, even though the sES of case-control studies described in previous SR articles indicated that HRT had a protective effect against lung cancer. It is necessary to conduct a pooled analysis of cohort studies.